The study of peculiarities of legal analogy in Russia of the civil law regime of dividends for commercial businesses - Viktor A. Mikryukov (Cogent Social Sciences)
Russian firms are facing sanctions imposed by foreign countries. These restrictions forced the corporations to suddenly refuse the distribution of profits or shift the timing of dividend payments. This unusual practice created the need for appropriate regulatory parameters for the net profit distribution mechanism to shareholders. These circumstances reflect significant gaps in the legal regime of dividends, as well as the lack of a unified doctrinal position on best practices in this area. This paper fills the gaps in the legal regulation of dividend policy, complicated by corporate specificity. Hence, this study aims to identify, analyze, and comprehensively investigate the areas of uncertainty in the regulatory mechanism that describes the adoption and implementation of dividend distribution policy for LLC and JSC, while testing the consistency of legal analogy as a strong protective tool in the corporate field. The methodology of this study was based on executing general logical techniques of analysis and synthesis of the order and terms of dividend payment, as well as determining the ways of casual overcoming these gaps using legal analogy. The results reflected that overcoming uncertainty in the legal regime of dividends of LLC and JSC promptly seems possible through active use of the analogy of law. This will make it possible not only to counteract the unfair, unreasonable, and unfair practice of freezing net profit but also to increase the lack of freedom to determine the frequency of announcements and ensure the mechanism flexibility for establishing the timing of actual dividend payments.